The Variation in the Essential Oil Composition of Tanacetum cadmeum (Boiss.) Heywood ssp orientale Grierson from Turkey - Polatoglu, Kaan; Goren, Nezhun; Baser, K. Huesnue Can; Demirci, Betuel (TAYLOR & FRANCIS INC, 2009)
Water-distilled essential oils from aerial parts of Tanacetum cadmeum (Boiss.) Heywood ssp. orientale Grierson, from two different localities in Turkey, were analyzed by GC and GC/MS. The flower, stern and root oils of T cadmeum ssp. orientale collected from the Adana location were characterized with a-thujone (25%, 5.2%), cis-linalool oxide (6.8%, 12.8%), trans-chrysanthenyl acetate (5.8%, 8.5%) for flower and stem oils, and beta-eudesmol (10.3%, 6.2%, 13.8%); in addition, stem oil contained 1,8-cineole (6.6%) and root oil contained hexadecanoic acid (6.0%), spathulenol (5.8%) and T-muurolol (5.3%). The flower and stem oils of T. cadmeum ssp. orientale collected front the Sivas location were characterized with camphor (25.9%, 14.8%), borneol (15.4%, 25.8%) and a-thujone (7.8%, 5.5%); in addition, stem oil contained 1,8-cineole (7.4%) and root oil contained nonacosane (16.2%), spathulenol (6.8%) and hexadecanoic acid (5.8%).
Keywords: Tanacetum cadmeum ssp cadmeum; Compositae; essential oil composition; camphor; borneol; alpha-thujone; beta-eudesmol; cis-linalool oxide; nonacosane; chemotypes; SCHULTZ BIP.; L.; Chemistry; Food Science & Technology